ANALISIS NUMERIK EFEK TUMBUKAN DAN POLA DEFORMASI CRASH BOX BERBENTUK ORIGAMI - Bismil Rabeta; Sahril Afandi S; Romario Fransisco (Jurnal Teknologi Kedirgantaraan, 2020)
Crash box is a longitudinal bar integrated with a bumper of the car is used to absorp the energy due to collision through a process of deformation (progressive buckling). The purpose of this analyis is to determine the response of the crash box when the subject to collision load with low speed. In addition, this analysis is also to determine the value of Pmax (peak force) against the geometry variations of the crash box that produce the value of theforce on the displacement and as a reference to determine the value of mean crushing force (Pmean) and crushing force efficiency (CFE). Every models has a different the value of mean crushing force (Pmean) and crushing force efficiency (CFE). In model 1 has a Pmean value of 12.976 kN and a CFE value of 0.584, Model 2 has a Pmean value of 10.458 kN and a CFE value of 0.789, and Model 3 has a Pmean value of 9.282 kN and a CFE value of 0.798.